2021
DOI: 10.3390/app11125748
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Changes Following Maxillary Expansion with Ni-Ti Leaf Springs Palatal Expander and Rapid Maxillary Expander: A Retrospective Study

Abstract: Background: The aim of this study is to evaluate and compare, through bidimensional cephalometry, skeletal and dental changes obtained from a rapid maxillary expander (RME) and a Ni-Ti leaf spring expander (Leaf) and compare them with an untreated control group. Methods: Records consisted of lateral cephalograms obtained before and after maxillary expansion of patients that underwent orthodontic treatment at the Department of Biomedical, Surgical and Dental Sciences. The Leaf expander group consisted of 9 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Furthermore, the results of the present study revealed that the occurrence of infraocclusion is more frequent in second primary molars; this anomaly has higher percentages in the mandibular arch than in the maxillary arch. In children with such developmental abnormalities, space issues might pose and in such cases expansion may become essential [ 18 , 29 , 30 ]. According to previous studies, the prevalence of mandibular infraocclusion was more than that of maxillary infraocclusion (189 : 36), and in the mandibular arch, the incidence is 2 to 10 times higher than that of the maxillary arch [ 1 , 2 , 21 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of the present study revealed that the occurrence of infraocclusion is more frequent in second primary molars; this anomaly has higher percentages in the mandibular arch than in the maxillary arch. In children with such developmental abnormalities, space issues might pose and in such cases expansion may become essential [ 18 , 29 , 30 ]. According to previous studies, the prevalence of mandibular infraocclusion was more than that of maxillary infraocclusion (189 : 36), and in the mandibular arch, the incidence is 2 to 10 times higher than that of the maxillary arch [ 1 , 2 , 21 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid maxillary expander (RME) and leaf expander have also been shown to produce maxillary expansion similar to dental and skeletal changes. 39 Furthermore, a transverse sagittal maxillary expander (TSME) can transversely cause a maxillary expansion in patients suffering from maxillary hypoplasia. 40 Last but not least, the option will be to surgically expose the canine and bring it to the arch orthodontically.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid maxillary expansion (RME) is an orthopedic procedure for the resolution of maxillary constriction in growing patients [ 9 ], whereas surgically assisted rapid maxillary expansion (SARME) is a treatment alternative for adult patients with a mature skeletal structure whose ossified sutures are resistant to orthopedics forces [ 10 ]. As reported by several authors, the age limit for orthopedic maxillary expansion is 14–18 years [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%